2017
DOI: 10.1007/s12678-017-0359-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of Pt-Ru/C Catalysts Prepared by Chemical Deposition for Direct Methanol Fuel Cells

Abstract: In this research, the activity and stability for methanol electro-oxidation on Pt-Ru/C catalysts was increased by optimising the catalyst preparation method. The Pt-Ru/C catalysts were synthesised using Pt(acac) 2 and Ru(acac) 3 precursors for chemical deposition of the metals. Performance of the catalyst was examined by cyclic voltammetry and chronoamperometry in a methanolcontaining electrolyte. TEM, EDS, X-ray photoelectron spectroscopy and XRD were used to physically characterise the catalysts. The paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
(53 reference statements)
0
8
0
1
Order By: Relevance
“…It has been reported that alloying Pt with Ru enhances notably the CO tolerance by two different effects, namely the electronic and the bifunctional effect. 9 In the electronic effect, Ru modifies the band structure of Pt, reducing its affinity towards CO, while in the bifunctional Ru helps in the catalysis of CO oxidation to CO 2 , which has a lower affinity for the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that alloying Pt with Ru enhances notably the CO tolerance by two different effects, namely the electronic and the bifunctional effect. 9 In the electronic effect, Ru modifies the band structure of Pt, reducing its affinity towards CO, while in the bifunctional Ru helps in the catalysis of CO oxidation to CO 2 , which has a lower affinity for the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…As hybrid automobiles embrace methanol fuel [1] , the methanol oxidation process is becoming more attractive for next-generation energy conversion systems [2] . However, the development of cheaper, stable catalysts with high performance in methanol oxidation reaction (MOR) is impeded by issues such as the necessity of using transition metals from the platinum group, ruthenium (Ru), iridium (Ir), palladium (Pd), platinum (Pt), or the poisoning of the Pt surface by carbon monoxide (CO) [3][4][5][6][7] . Nevertheless, as in the case of H 2 proton-exchange membrane fuel cells [8] , in certain conditions (e.g., low amounts of platinum on anode and cathode catalysts), the methanol fuel cell costs could be made manageable for large scale commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel cells, as clean and renewable energy conversion devices, have become a subject of extensive research interest due to their high power density, high energy efficiency, low operating temperature, and easy storage and transportation. [1][2][3] So far, Ptbased materials are considered to be the most effective electrocatalysts for fuel cells. However, Pt is scarce and expensive, and the kinetics of small organic molecule electro-oxidation on Pt is still relatively sluggish.…”
Section: Introductionmentioning
confidence: 99%
“…Ni and Co alloyed with Pt to increase the electrocatalytic activity, 26 and Ru improved the anti CO poisoning performance. 3 PtCoNiRu quaternary alloy NPs were synthesized and evenly dispersed on the modified Vulcan XC-72 surface with high loading capacity by spray drying combined with reduction sintering. The inner structure and the electrochemical activities for MOR of the as-synthesized alloy NPs were investigated.…”
Section: Introductionmentioning
confidence: 99%